กระบวนการบริหารโครงการออกแบบเพื่อก่อสร้างสถานเอกอัครราชทูตไทยในต่างประเทศ - ลลิตา เจียมวัฒนศิริกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
To design and construct Royal Thai Embassies, which are governmental structures outside Thailand, procurement must be conducted using a special methodology. Moreover, the construction projects are affected by a number of highly uncontrolled factors, unlike governmental buildings in Thailand. According to primary research, several ongoing Royal Thai Embassy projects are facing construction delay problems.This study aims to study the problems of the Royal Thai Embassy design and construction process from the inception period to contractor procurement. The research methodology begins with reviewing the architectural project management theories and study design process from 4 case studies. The four case studies were projects initiated 6 years ago which are still ongoing: 1) The Royal Thai Embassy, China 2) The Royal Thai Embassy, India 3) The Royal Thai Embassy, Pakistan 4) The Royal Thai Embassy, Japan. Interviews were also conducted with authorities in the property department of the Ministry of Foreign Affairs and with project architects.The findings indicate that the projects can be initiated by Royal Thai Embassy officers or as a result of property department plans. After proposing a budget, an architectural firm will be hired with a specified design fee. Then, from the design phrase and construction approval, the process moves on to the contractor procurement period with advice from a Thai architect. The architect’s liability ends in this stage and the responsibility will pass forward to the construction manager. The problems found in the process stem from design revisions due to the change of area requirements and revisions by the local architect which may result in delays. Furthermore, the local processes and regulations regarding construction approval are different and complex, which affects the project timeframe.Based on the findings, the following recommendations can be made. First, the Ministry of Foreign Affairs should hire a project manager to be an owner/representative in addition to creating a project plan, leading and controlling the project. Secondly, embassy project management guidelines should be established for authorities to implement along with properly information preparation. Next, the Thai architect’s design fee should be properly adjusted to the scope of services with additional fees being clearly specified in the design contract. Lastly, a design control committee should be arranged to approve the main design concept and keep it on track without unnecessary changes.